SOSIALISASI PENGARUH ”GADGET” PADA ANAK USIA DINI DI TK AL-MUNAWWARAH KOTA BANDUNG - Mia Tania; Enung Nurhayati, Nazmi Abdurahman, Deli Luthfi Rahman (Adiba Aisha Amira, 2023)
This article aims to both investigate and discuss how socialization process of the influence of gadget gives impact to the growth of pre-school children. It is viewed from two prespectives of knowledge, namely digital business and communication studies, which are applied on parents in pre-school institution. Massive development of information technology and internet has indirectly forced future-generation to be able to be adaptive and responsive on technology. The way of gadget works has impacted to how people react on fulfilling their own daily needs, including managing things on children’s learning and playing activities. The use of gadget should be under the supervision and guidance of parents, to prevent the children be influenced by negative and deviant things. Therefore, a role of parents is required to overcome this problem effectively. This prevention can also limit children’s access to gadgets, select appropriate applications (age-friendly), choose educational contents (shows or games) for their children, and provide assistance when children access something through their gadgets.